2014
DOI: 10.5539/ijms.v6n6p91
|View full text |Cite
|
Sign up to set email alerts
|

The Corporate Reputation of Islamic Banks: A Measurement Scale

Abstract: During the last few years, the concept of corporate reputation has received considerable attention from marketing academics and practitioners alike. This is not surprising in view of the concept enormous practical implications. Suffice it to say, that the market value of a modern company lies mainly in its intangibles assets. Corporate reputation embodies all of the intangible capital that a company may have. The current study describes an attempt to develop and validate a scale to measure the corporate reputa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Seventhly, the ethics of the Islamic banking brand could be the solution to consider in order to expand the market share of these institutions in Western financial markets, even where consumers are not Muslim. This is in line with Almahy et al's (2014) contribution to the importance of Islamic finance in today's economy (Almahy et al, 2014).…”
Section: Theoretical Contributionssupporting
confidence: 88%
See 2 more Smart Citations
“…Seventhly, the ethics of the Islamic banking brand could be the solution to consider in order to expand the market share of these institutions in Western financial markets, even where consumers are not Muslim. This is in line with Almahy et al's (2014) contribution to the importance of Islamic finance in today's economy (Almahy et al, 2014).…”
Section: Theoretical Contributionssupporting
confidence: 88%
“…The practice of usury, including bank interest, is forbidden, as is speculation (Ahmad, 2000). In line with Almahy et al (2014), Islamic banking can be seen as an alternative to the crises of conventional debt-based financing models promoted by Western financial institutions. It represents an alternative financial system, in line with Islamic principles, proposing interest-free finance, promoting justice and helping to strengthen social cohesion (Almahy et al, 2014).…”
Section: Theoretical Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is essential to view reputation as a "collective representation" of images and opinions about a business, and not to view it as a "self-promoted message". This includes connections with all shareholders, and it may be gained, preserved and improved or diminished over time (Almahy et al, 2014). Ahmad et al (2015) studied customers' behaviors toward Islamic banks in Pakistan and they found that reputation was the main factors for customers when selecting a bank.…”
Section: Reputationmentioning
confidence: 99%
“…Islamic banking is seen as a response to the crises of conventional debt-based financing models promoted by Western financial institutions, an alternative financial system respectful of its Islamic principles, offering interest-free finance, promoting justice, and fostering social cohesion (Almahy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%